Effect of service quality on savings customer satisfaction at Bank Muamalat Indonesia Kediri - Ani Sulsiah (Central Research Institute for Agriculture (CeRIA), 2022)
This study aims to analyze the significant influence of service quality variables simultaneously and partially on customer satisfaction and to analyze service quality variables that have the most dominant effect on customer satisfaction. The type of research used is survey research with five independent variables, namely: physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) and the dependent variable, namely customer satisfaction (Y). This research was conducted at Bank Muamalat Indonesia Kediri using a sample of 100 customers. The sampling technique uses purposive sampling. The data source uses primary data, namely the results of questionnaires and secondary data, namely documentation materials. Methods of data collection using questionnaires and interviews. The data analysis tool used is multiple linear regression analysis. To determine the effect of each of these variables, multiple linear regression tests and other tests are used to strengthen the results of the analysis of this study. From this study it is known that each variable consists of physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) which have a simultaneous and partial influence on customer satisfaction (Y). Responsiveness variable (X3) is a variable that has a dominant influence on customer satisfaction at Bank Muamalat Indonesia Kediri.